Association between the Y balance test and knee valgus moments during an unplanned sidestep cut : implications for Acl injury prevention - Yeo, Jie Min (2016)
Association Between The Y Balance Test And Knee Valgus Moments During An Unplanned Sidestep Cut: Implications For Acl Injury Prevention